Construction Risk Assessment of Tunnel Crossing Goaf Based on Analytic Hierarchy Process‐Extension Theory Model - Chao Yuan; Lian‐xin Li; Xiao‐wei Su; Rong‐jie Du (Energy Science & Engineering)
ABSTRACT In the tunnel construction project, it is possible to encounter coal mine goaf. The goaf is often accompanied by a large number of toxic and harmful gases such as gas, carbon monoxide and carbon dioxide. These factors undoubtedly increase the occurrence of geological disaster risk accidents such as gas combustion and explosion, resulting in tunnel excavation shutdown, plan delay and even a large number of casualties. To grasp the risk status of tunnel construction safety in coal mine goaf, we selected 11 risk factors as evaluation indicators on the basis of investigation and analysis of risk factors in a large number of engineering cases of tunnel crossing coal mine goaf. The construction risk evaluation indicator system of tunnel crossing coal mine goaf is constructed, the weight of construction risk evaluation indicator is calculated, and the risk evaluation grade of tunnel construction is determined. On this basis, the construction risk assessment judgment matrix is established by using the analytic hierarchy process, and the calculation system of the weight of each indicator in the risk assessment system is developed by using the Java programming language. Based on the theory of extension evaluation, a matter‐element extension model for the construction risk assessment of tunnel crossing coal mine goaf is established, and the construction risk assessment of Wanmin tunnel is carried out by using this model. The results of risk assessment grade provide an important theoretical basis and guidance for the selection of safe construction methods for subsequent tunnels crossing coal mine goaf. The successful application of the matter‐element extension model established in this paper provides a new idea for the quantitative evaluation of the construction risk of tunnel uncovering coal mine goaf.